2017
DOI: 10.1177/1055665617735102
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Velopharyngeal Dysfunction

Abstract: Objective: This systematic review sought to evaluate the consensus in the literature regarding the surgical management of VPD and to determine whether a particular procedure results in superior speech outcome or less morbidity Design: A systematic review was carried out according to PRISMA-P guidelines. Systematic review software was used to facilitate 3-stage screening and data extraction by 2 reviewers.Setting: University teaching hospital.Patients, Participants: Studies that reported perceptual speech asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 78 publications
(71 reference statements)
2
56
0
Order By: Relevance
“…Complication rates. Pharyngeal flaps are the most commonly reported procedure for VPI (49% of studies), with the highest rates of OSA (5.1%) and lowest rates of revisional surgery required (6.1%; de Blacam et al, 2018). A recent study using the 2012 American College of Surgeons National Surgical Quality Improvement Program Pediatric database identified the overall perioperative complication rate for posterior pharyngeal flap surgery to be low (5.3%) and identified patients with underlying cardiac risk factors, severe American Society of Anesthesiologists Physical Status class, and asthma as having heightened risk profiles (Swanson et al, 2016) Our major complication rate of 3% OSA and 3% rate of reoperation compare favorably to these studies in the literature.…”
Section: Outcomes/complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complication rates. Pharyngeal flaps are the most commonly reported procedure for VPI (49% of studies), with the highest rates of OSA (5.1%) and lowest rates of revisional surgery required (6.1%; de Blacam et al, 2018). A recent study using the 2012 American College of Surgeons National Surgical Quality Improvement Program Pediatric database identified the overall perioperative complication rate for posterior pharyngeal flap surgery to be low (5.3%) and identified patients with underlying cardiac risk factors, severe American Society of Anesthesiologists Physical Status class, and asthma as having heightened risk profiles (Swanson et al, 2016) Our major complication rate of 3% OSA and 3% rate of reoperation compare favorably to these studies in the literature.…”
Section: Outcomes/complicationsmentioning
confidence: 99%
“…Incomplete closure during speech leads to air escape causing hypernasality, increased nasal resonance, and decreased intelligibility (Ruda et al, 2012). Furthermore, children with untreated VPI may develop secondary sequelae, including compensatory speech misarticulations (glottal stops and pharyngeal fricatives), softness of voice, and laryngeal nodules due to increased laryngeal airflow (Hogan, 1973;Kummer et al, 2015;de Blacam et al, 2018). Decreased intelligibility from VPI adversely affects patients' schooling, work, and psychosocial health and negatively impacts children's quality of life (Sloan, 2000;Leclerc et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews performed in this area [3] have identified significant diversity of methodology and reporting of results. Consequently, it is anticipated that there will be substantial heterogeneity and that a formal meta-analysis will not be feasible.…”
Section: Datamentioning
confidence: 99%
“…13 The majority of studies in the literature report perceptual speech assessment using a nonvalidated, in-house scale. 14 The diagnosis of VPI must be multidisciplinary: speech and instrumental assessment must be combined. Regarding instrumental assessment, every institution chose between a combination of nasoendoscopy (NE) alone, multiplanar videofluoroscopy (MPVF) alone or a combination of the two.…”
Section: Introductionmentioning
confidence: 99%